1997
DOI: 10.1136/bmj.314.7075.174
|View full text |Cite
|
Sign up to set email alerts
|

Popularity of less frequent follow up for breast cancer in randomised study: initial findings from the hotline study

Abstract: Objectives: To study the ictal phenomenology, aetiology, and outcome of convulsions occurring within seconds of impact in violent collision sport. Design: Retrospective identification of convulsions associated with concussive brain injury from case records from medical officers of football clubs over a 15 year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 22 publications
4
123
0
3
Order By: Relevance
“…From these abstracts, six full-length articles were obtained, all of which were eligible for inclusion in the analysis (Grunfeld et al, 1996Gulliford et al, 1997;Brown et al, 2002; Koinberg et al, 2004; Kokko et al, 2005). One abstract had been published as part of the proceedings of a scientific meeting and the data had not yet been published in full (Baildam et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From these abstracts, six full-length articles were obtained, all of which were eligible for inclusion in the analysis (Grunfeld et al, 1996Gulliford et al, 1997;Brown et al, 2002; Koinberg et al, 2004; Kokko et al, 2005). One abstract had been published as part of the proceedings of a scientific meeting and the data had not yet been published in full (Baildam et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, similar numbers in the high-and low-frequency groups will express a desire for lower-or higher-frequency visits than they received during the trial (Gulliford et al, 1997). In the trial by Baildam et al (2004), the Fallowfield Satisfaction with Consultation Questionnaire revealed that women were significantly more satisfied with their consultation with a nurse than those seen by a doctor (Po0.001).…”
Section: Satisfactionmentioning
confidence: 93%
See 3 more Smart Citations